Pairing between stimuli and vocal imitation in children with Autism Spectrum Disorder:Assessment of the role of guidance responses (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
In SSP (stimulus-stimulus pairing), a target sound is paired with an item or eventpreferred by a child. As a possible result, children begin to imitate the presented sound.This study evaluated the effects of the guidance component on the effectiveness of SSP(stimulus-stimulus pairing) in children with ASD. A multiple baseline design acrossparticipants was used. Three children were subjected to two types of SSP: (A) withoutthe requirement for an orienting response to the stimuli, and (B) SPP with therequirement for an orienting response. Sessions were held lasting 10 minutes, with a 1-minute interval between pairings. P3 and P2 had an increase in responses in B. For P1the result was the opposite, there was greater vocalization of target responses in A. Thedata suggest relevance to the participants' initial repertoire, and consider that theincrease in vocalizations may involve operant contingencies.
Keywords: vocal imitation; pairing; guidance responses; autism.